Philosophical and methodological trends in geography: Philosophical and methodological trends in geography (jornal of the libyan geographical society, 1996)
Geography has gone through multiple stages in its intellectual development from ancient times to the present day. In each of these stages, new methodological trends emerged based on the philosophies embraced by geographers at that time.The main objective of this research is to identify the philosophical and methodological trends that prevailed in each stage of the development of geography. In pursuit of this main objective, we will discuss a range of critical issues and problems, such as the topic of the unity or multiplicity of methodologies in geography.The issue of disagreement between supporters of using the positivist scientific method and supporters of other methods that emphasize subjectivity and are followed in human studies such as the historical method and the cognitive method. We will also address the relationship of geography to other sciences and the methods used in them, and will try to highlight the most important philosophical and methodological revolutions in geography.The method used in this research to address these issues will be by reviewing geographical literature and discussing the most important philosophical schools and methodological approaches used in each stage of the development of geographical thought, with a focus on the clear trends that characterize each period and highlighting the contributions of the most important geographers in that period.
Keywords: Methodology; philosophical trends; scientific method